Making Sense of Primary School Homework: A feminist study of mothers' constructions of homework support - Lehner-Mear, Rachel (2023)
Homework is a near-universal practice in UK primary schools (Medwell & Wray, 2019), principally studied from the perspective of what it may add to academic outcomes (H.Cooper et al., 2006; Jerrim et al., 2019; Ozyildirim, 2021). Limited research considers homework as a practice within the home, particularly viewed from the perspective of mothers, who are often the parent most closely involved in its support (Hutchison, 2012; Mandell & Sweet, 2004; Warton, 1998). This thesis uses theories of mothering to understand gendered homework labour from the individual standpoints of eight mothers.